2022
DOI: 10.1002/smll.202200125
|View full text |Cite|
|
Sign up to set email alerts
|

Elucidating Design Principles for Engineering Cell‐Derived Vesicles to Inhibit SARS‐CoV‐2 Infection

Abstract: The ability of pathogens to develop drug resistance is a global health challenge. Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) presents an urgent need wherein several variants of concern resist neutralization by monoclonal antibody (mAb) therapies and vaccine‐induced sera. Decoy nanoparticles—cell‐mimicking particles that bind and inhibit virions—are an emerging class of therapeutics that may overcome such drug resistance challenges. To date, quantitative understanding as to how design features… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 80 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…In addition, mutant SARS‐CoV‐2 strains that were resistant to mAb antibodies and sACE2 inhibitors, as well as Delta and Lambda, were all effectively inhibited by this nanodecoy strategy. This study shows that the antiviral effects of a nanodecoy containing ACE2 may be unaffected by the type of EVs or the purification technique used, and that, given the benefits, NVs could be a good substitute (Gunnels et al., 2022).…”
Section: Defence: Evs As a Nanodecoy To Defend Against Sars‐cov‐2 Col...mentioning
confidence: 87%
“…In addition, mutant SARS‐CoV‐2 strains that were resistant to mAb antibodies and sACE2 inhibitors, as well as Delta and Lambda, were all effectively inhibited by this nanodecoy strategy. This study shows that the antiviral effects of a nanodecoy containing ACE2 may be unaffected by the type of EVs or the purification technique used, and that, given the benefits, NVs could be a good substitute (Gunnels et al., 2022).…”
Section: Defence: Evs As a Nanodecoy To Defend Against Sars‐cov‐2 Col...mentioning
confidence: 87%
“…It has been proposed that excess soluble ACE2 could bind to the S spike protein on the SARS-COV-2 virus, neutralizing the virus and preventing its fusion to the host membrane. Interestingly, Gunnels et al (2022) with low amounts of ACE2-positive exosomes, suggesting the protective efficacy of ACE2-positive exosomes (Ching et al, 2022).…”
Section: Exosomes As a Viral Decoymentioning
confidence: 98%
“…New COVID-19 VOCs provide challenges when designing therapeutics employing decoy strategies. Gunnels et al identified a Beta mutant consisting of three mutations in its receptor binding domain making it resistant to FDA approved mAbs (K417N, E484K, N501Y) that inhibit its interaction with the host ACE2 (Gunnels et al, 2022). These mutations increase affinity of the spike protein for the host ACE2 by three folds.…”
Section: Limiting the Binding Of Viral Particles Using Nanodecoys And...mentioning
confidence: 99%